2016
DOI: 10.1111/pai.12589
|View full text |Cite
|
Sign up to set email alerts
|

How relevant is panallergen sensitization in the development of allergies?

Abstract: Panallergens comprise various protein families of plant as well as animal origin and are responsible for wide IgE cross‐reactivity between related and unrelated allergenic sources. Such cross‐reactivities include reactions between various pollen sources, pollen and plant‐derived foods as well as invertebrate‐derived inhalants and foodstuff. Here, we provide an overview on the most clinically relevant panallergens from plants (profilins, polcalcins, non‐specific lipid transfer proteins, pathogenesis‐related pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 72 publications
1
43
0
Order By: Relevance
“…The use of component‐resolved diagnostics facilitates the understanding of PFS, leading to a new classification based on panallergen IgE sensitization profiles . Moreover, the IgE sensitization to panallergens can be used as predictor for cross‐reactive allergy and as biomarker for disease severity …”
Section: Biomarkers Of Disease Severitymentioning
confidence: 99%
“…The use of component‐resolved diagnostics facilitates the understanding of PFS, leading to a new classification based on panallergen IgE sensitization profiles . Moreover, the IgE sensitization to panallergens can be used as predictor for cross‐reactive allergy and as biomarker for disease severity …”
Section: Biomarkers Of Disease Severitymentioning
confidence: 99%
“…Pollen‐induced AR commonly correlates with oral symptoms after eating raw fruit, vegetables, and seeds (pollen‐food syndrome), including labial and oropharyngeal pruritus and angioedema. This condition reflects the presence of IgE cross‐reactivity between epitopes in pollen allergens, named ‘panallergens’, and homologous proteins in certain foods . A new pollen‐food syndrome classification based on panallergen IgE sensitization profiles identified specific endotypes with the aim of developing tailored prevention and treatments in childhood .…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…53 Profilins are a widespread family of highly cross-reactive allergens which have been isolated in a large number of sources, so much so that this allergen is considered a true panallergenic molecule. 54 Xiao et al synthesized a complex containing PLGA with a recombinant profilin from Caryota mitis (rCmP). The Authors showed that the rCmP-loaded PLGA NPs effectively inhibited the generation of allergen-specific IgE and the secretion of the proinflammatory Th2 cytokine IL-4, facilitating the generation of allergen-specific IgG2a and the secretion of the Th1 cytokines in vivo.…”
Section: Pollen Allergensmentioning
confidence: 99%
“…55 The same NPs were employed in a different immunotherapy regimens by Salari et al, targeting another relevant cross-reactive allergen, Che a 3 protein belonging to the polcalcin family, an allergen showing high levels of identity with polcalcin from olive, birch, alder, rapeseed, and timothy grass pollens. 54 BALB/c mice were sensitized to rChe a 3 and then treated sublingually, either with soluble rChe a 3 or PLGA-encapsulated rChe a 3.…”
Section: Pollen Allergensmentioning
confidence: 99%